To build oneself for education. Paths of educommunication - Prieto Castillo, Daniel (2017)
In this essay I work on what it means to build oneself in a communicational manner for education, from my experience of the last 30 years in relation to training proposals for university colleagues. From a recurring idea of 'forming', we recover the memory of Simon Rodriguez to think about 'building'. To achieve this path, we dwell on two concepts developed during the labour of the last decades: pedagogical mediation and the parallel text as a method.